2011
DOI: 10.1167/iovs.11-8600
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Cone Structure in Foveal Schisis Cavities in X-Linked Retinoschisis from Mutations in Exon 6 of theRS1Gene

Abstract: AOSLO images of two patients with molecularly characterized XLRS revealed increased cone spacing and abnormal packing in the macula of each patient, but cone coverage and function were near normal outside the central foveal schisis cavities. Although cone density is reduced, the preservation of wave-guiding cones at the fovea and eccentric macular regions has prognostic and therapeutic implications for XLRS patients with foveal schisis. (Clinical Trials.gov number, NCT00254605.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 84 publications
0
27
0
Order By: Relevance
“…Although previous studies 34,35,[41][42][43][44][45][46][47][48][49][50][51][52] have used AOSLO to assess cone spacing and density in normal and diseased eyes, none have reported on how foveal cone measures and visual function are correlated. The present study demonstrates a significant correlation between increased AOSLO cone spacing Z-scores and decreased VA at or near the fovea, as well as a significant correlation between Z-scores and foveal sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies 34,35,[41][42][43][44][45][46][47][48][49][50][51][52] have used AOSLO to assess cone spacing and density in normal and diseased eyes, none have reported on how foveal cone measures and visual function are correlated. The present study demonstrates a significant correlation between increased AOSLO cone spacing Z-scores and decreased VA at or near the fovea, as well as a significant correlation between Z-scores and foveal sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…34,35,[41][42][43][44][45][46][47][48][49][50][51][52] Adaptive optics-based studies 41,42 of retinal degeneration showed a significant correlation between macular cone spacing and central visual function, but given the small size and unique anatomy 53 of foveal cones and the resulting difficulties posed on imaging, 54 these studies were unable to assess cone morphology at the foveal center. Within the past few years, advanced systems that have implemented improvements in AO scanning laser ophthalmoscopy (AOSLO) system design 55 and advanced controls 56 have been able to more routinely visualize the foveal cone mosaic.…”
mentioning
confidence: 99%
“…These structures are also found in animals following ablation of Müller glial cells (Byrne et al, 2013), in association with defects in the outer limiting membrane (Stuck et al, 2012), in conditions where microRNA function is disrupted (Damiani et al, 2008) and when cell proliferation is abnormal (Lin et al, 2001). Gross perturbation to retinal organization is also evident in patients and animal models with retinoschisis, a condition that leads to a physical separation between cells at the level of the OPL, resulting from the loss of the protein retinoschisin (Duncan et al, 2011; Kjellstrom et al, 2007; Molday et al, 2012; Takada et al, 2008). …”
Section: Disease: Alterations To Structure and Functionmentioning
confidence: 99%
“…Using AOSLO, Duncan et al reported increased cone spacing and abnormal packing in the macula of XLRS patients [22]. Baseline images taken prior to treatment also exhibited qualitative abnormalities – dark spacing and mottling of the mosaic – when compared to a similar area in an unaffected control (Figure 5).…”
Section: Discussionmentioning
confidence: 99%